Kehidupan Sosial Ekonomi Petani Padi Sawah di Desa Rompegading Kecamatan Liliriaja Kabupaten Soppeng - Try Hardianti; Hasriyanti Hasriyanti; Nasiah Badwi (Universitas Negeri Makassar, 2020)
This study aims to determine. The income level of lowland rice farmers in Rompegading Village, Liliriaja District, Soppeng Regency and the socio-economic life of rice farmers in Rompegading Village, Liliriaja District, Soppeng Regency. Data collection was carried out through observation, questionnaires and documentation. With descriptive analysis data processing techniques. The population in this study were 673 farmers, while the sample of this study was 42 farmers. The results showed that the income level of lowland rice farmers in Rompegading village was able to meet all the needs of farmers in the village where the largest income came from farming activities and a small portion came from activities outside of farming and the socio-economic life of farmers in Rompegading village can be said to be at a moderate level of welfare. This is because most of the farmers have sufficient income, decent housing, good health and education facilities and are safe from the threat of crime.